Phage‐mediated horizontal transfer of Salmonella enterica virulence genes with regulatory feedback from the host - Tianjing She; Demeng Tan; Jose Luis Balcazar; Ville‐Petri Friman; Danrui Wang; Dong Zhu; Mao Ye; Mingming Sun; Shujian Yuan; Feng Hu (iMeta)
Abstract Phage‐mediated horizontal transfer of virulence genes can enhance the transmission and pathogenicity of Salmonella enterica (S. enterica), a process potentially regulated by its regulatory mechanisms. In this study, we explored the global dynamics of phage‐mediated horizontal transfer in S. enterica and investigated the role of its regulatory mechanisms in transduction. A total of 5178 viral sequences encoding 12 S. enterica virulence genes were retrieved from the Integrated Microbial Genomes and Virome (IMG/VR) database, alongside 466,136 S. enterica genomes from EnteroBase. Virulence genes, including iacP (acyl carrier protein), mgtB (P‐type Mg2+ transporter), misL (autotransporter porin), and fliC (flagellar filament protein), were widely distributed in phages and S. enterica across North America, Europe, and Asia. Phylogenetic analysis revealed close genetic affinity between phage‐ and bacterial‐encoded virulence genes, suggesting shared ancestry and historical horizontal gene transfer events. The global regulator carbon storage regulator A (csrA) was highly conserved and ubiquitous in S. enterica. Overexpression of csrA inhibited prophage cyclization and release by upregulating the prophage cI repressor during horizontal gene transfer. Overall, these findings enhance our understanding of phage‐mediated horizontal transfer of virulence genes, explore new areas of bacterial regulators that inhibit gene exchange and evolution by affecting phage life cycles, and offer a novel approach to controlling the transmission of phage‐mediated S. enterica virulence genes.